Unlocking the Human Capital Paradox: Innovation Culture and Organizational Competence as Dual Mediators of Institutional Performance in Indonesian Private Business Colleges - Tutik Winarsih; Fariz Fariz (Eastasouth Institute, 2026)
Private higher education institutions in Indonesia, particularly Sekolah Tinggi Ilmu Ekonomi (STIE) in East Java, face a human capital paradox in which a high proportion of doctoral-qualified staff does not automatically improve institutional performance. Grounded in Resource Orchestration Theory and Dynamic Capability View, this study examines whether Innovation Culture mediates the relationship between Human Capital Readiness and Organizational Performance, and whether Organizational Competence mediates the relationship between Organizational Learning and Organizational Performance. Using a quantitative cross- sectional design and PLS-SEM, data were collected from 312 permanent lecturers and structural officials across 38 accredited STIEs in East Java. The findings show that Innovation Culture fully mediates the Human Capital Readiness–Organizational Performance relationship, while Organizational Competence partially mediates the Organizational Learning–Organizational Performance relationship. These results confirm the Value-Activation Model and show that strategic resources produce measurable performance only when activated through cultural and competence-based mechanisms. The study offers practical direction for STIE leaders seeking to improve institutional performance under resource constraints.